2008
DOI: 10.1002/pc.20366
|View full text |Cite
|
Sign up to set email alerts
|

Structure–properties of electron beam irradiated and dicumyl peroxide cured low density polyethylene blends

Abstract: Low density polyethylene (LDPE) and its blends with styrene butadiene rubber and ethylene propylene diene monomer were cured, using electron beam irradiation as well as dicumyl peroxide (DCP). The effect of blending was found to change the melt viscosity when compared with the virgin LDPE. Also, the influence of curing system on the various properties was investigated. It was found that either irradiation or DCP curing enhanced the gel content and crosslink density as well as the mechanical and hot set propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Gel content data are used to estimate the crosslink density of irradiated polymeric materials 26. The gel content of the compatibilized LLDPE/soya powder blends with 30 kGy irradiation is shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Gel content data are used to estimate the crosslink density of irradiated polymeric materials 26. The gel content of the compatibilized LLDPE/soya powder blends with 30 kGy irradiation is shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…In general the IR absorption bands of PVA are all quite broad and overlapped in the 600-1600 cm -1 region. In the spectra of pure PVA and ZnO/ PVA nanocomposites, the broad strong absorption band at ~ 3000-3600 cm −1 is assigned to the stretching vibration of hydroxyl group (OH) [14].The FTIR spectrum of PVA shows the bands at about~2940, 1317, 1088, 940 and 845 cm -1 were attributed to the asymmetric -CH2 stretching, C-O and CH2 rocking vibration, C-C stretching vibration groups of PVA, respectively [15,16]. As ZnO content in all nanocomposite samples increases the hydroxyl peak shifted from 3459 to 3515 cm -1 , which is due to the strengthening of hydrogen bonds present in ZnO and PVA matrix.…”
Section: Structural and Spectroscopic Properties Ofmentioning
confidence: 99%
“…9 Figure 1 describes the relationship between tensile strength and either the HCB content or irradiation dose for LDPE/HCB and LDPE/iPP/HCB formulations. 6,7 The presence of HCB in the polymeric composite formulations, which is represented as a cross-linking agent, results in reinforcements of tensile strength, since it becomes a source of cross-link initiation, which contributes to cross-linking rather than degradation. 1a, it can be clearly observed that the tensile strength increases gradually with increasing either the irradiation dose or HCB content.…”
Section: Mechanical Properties Of Polyolefin Composite Formulationsmentioning
confidence: 99%
“…At higher irradiation doses, a large number of radicals are formed, which are expected to yield higher gel content. 7 Radiationinduced cross-linking of polymeric samples might be formed via combination of either the macroradicals formed from polymeric chains or between and throughout the formed radicals from HCB. In addition, the degree of cross-linking is affected by the compatibility effect of HCB between the polymer sample components.…”
Section: Gel Contentmentioning
confidence: 99%
See 1 more Smart Citation